Elizabethkingia miricola Causes Intracranial Infection: A Case Study - Gao, Hongguang; Li, Tian; Feng, Li; Zhang, Shu (Frontiers in Medicine, 2021)
Background:Elizabethkingia miricola is a rarely encountered bacterium in clinical practice. It is a rare gram-negative rod-shaped bacterium associated with lung and urinary tract infections, but never found in cerebrospinal fluid. This paper reports a case of an adult patient infected by E. miricola via an unknown route of infection causing a severe intracranial infection. Elizabethkingia miricola was detected by culture and Metagenomic next generation sequencing in CSF. Early identification of this strain and treatment with sensitive antibiotics is necessary to reduce morbidity and mortality. Case Report: A 24-year-old male was admitted to a West China Hospital because of headache and vomiting for 2 months. Symptom features included acute onset and long duration of illness. Notably, headache and vomiting were the primary neurological symptoms. Routine cerebrospinal fluid culture failed to identify the bacterium; however, Elizabethkingia miricola bacterium was detected via second-generation sequencing techniques. Elizabethkingia miricola was found to be a multi-drug resistant organism, hence, treatment with ceftriaxone, a commonly used drug for intracranial infections was ineffective. This strain eventually caused severe intracranial infection resulting in the death of the patient. Conclusion: In summary, this study comprehensively describes a case of an adult patient infected by E. miricola and discusses its early identification as well as application of sensitive antibiotics in the emergency setting.